Value Of Uric Acid In Patients With Chronic Kidney Disease In Pre-Dialysis Stage - Egamberdieva Dano Abdisamatovna, Daminov Botir Turgunpulatovich, Ruzmetova Iroda Arslanovna (International Journal of Advanced Science and Technology, 2020)
The study examined the relationship between uric acid levels and renal function, aswell as its role as a prognostic marker of cardiovascular risk in chronic kidney disease. In amultivariate regression analysis, taking into account the adjustment of potential risk factors, thelevel of uric acid was a significant factor affecting the glomerular filtration rate. The results ofthe study showed that elevated serum uric acid levels are associated with a higher risk of renaldysfunction.